Literature Review Transformative, Servant, and Digital Leadership: Shaping the Future of Education in Indonesia - Sianipar, Benny Haposan; Nabila, Alifah Biggum; Jalinus, Nizwardi; Ernawati, Ernawati (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study aims to systematically examine the leadership principles applied in educational institutions in Indonesia and their impact on the quality of education. The study used the conducted using the Systematic Literature Review (SLR) approach on 15 scientific articles from SINTA-indexed journals 1 to 3 published between 2018-2024. The analysis was conducted thematically using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) model. The results show that transformational leadership and servant leadership are the most dominant approaches in educational leadership studies, followed by digital leadership, which has begun to develop in recent studies. These leadership practices have been proven to contribute to improvements in teacher performance, learning innovation and the effectiveness of education policy implementation. However, most of the studies remain descriptive and qualitative, lacking optimal integration of leadership theory with national policy directions. This study emphasizes the need to develop a contextualized, adaptive to technological developments and based on data, as a strategic effort to support the transformation of education in Indonesia.